-20+12r+6q-2r-3q-26=

Simple and best practice solution for -20+12r+6q-2r-3q-26= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -20+12r+6q-2r-3q-26= equation:


Simplifying
-20 + 12r + 6q + -2r + -3q + -26 = 0

Reorder the terms:
-20 + -26 + 6q + -3q + 12r + -2r = 0

Combine like terms: -20 + -26 = -46
-46 + 6q + -3q + 12r + -2r = 0

Combine like terms: 6q + -3q = 3q
-46 + 3q + 12r + -2r = 0

Combine like terms: 12r + -2r = 10r
-46 + 3q + 10r = 0

Solving
-46 + 3q + 10r = 0

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '46' to each side of the equation.
-46 + 3q + 46 + 10r = 0 + 46

Reorder the terms:
-46 + 46 + 3q + 10r = 0 + 46

Combine like terms: -46 + 46 = 0
0 + 3q + 10r = 0 + 46
3q + 10r = 0 + 46

Combine like terms: 0 + 46 = 46
3q + 10r = 46

Add '-10r' to each side of the equation.
3q + 10r + -10r = 46 + -10r

Combine like terms: 10r + -10r = 0
3q + 0 = 46 + -10r
3q = 46 + -10r

Divide each side by '3'.
q = 15.33333333 + -3.333333333r

Simplifying
q = 15.33333333 + -3.333333333r

See similar equations:

| 0/27=x | | 2(a+2b)-(a-b)= | | 9+4r=1 | | 19=19h-19 | | 5=v+1 | | 1/6d+2/3=1/4(d-2) | | -4+15=11 | | sinA=0.5 | | 7x-8-5x=0 | | 118=-5(-4-4p)-6p | | -4+15=x | | 7c-2c=42 | | x-6-17=-13 | | -7z+4+16-8z= | | X^3-6x+10x-8=0 | | 15=12k-9 | | a+(a+10)=16 | | -4c+9(3c+5)= | | 10p+18=-12 | | 13q+48=-3q | | -12(-5c-6)= | | 6+5(-3a+8)=136 | | -2=1n+2 | | 2x^4+2x^3+x^2=656 | | x-2(6.5+3.5x)=11 | | -9(5+2f)= | | -5x-7x+3+6= | | 2x-39=21 | | 8t+1=-7 | | 3(-12)-6=42 | | 50=x+y*2x | | 9-4z=1 |

Equations solver categories